Enteroparásitos en hortalizas expendidas en el mercado Central de Moyobamba, San Martín – Perú, 2021 - Calderón Salazar, Anthony (2023)
Eating vegetables prepared as salads is a quick, easy and healthy source of nutrition; however, they can also be a source of infection by foodborne protozoa and intestinal helminths, if they are contaminated, which is increasingly being recognized as a global threat recently, despite their consideration for their energy supply and non-pharmacological prophylaxis against various diseases. The objective of the present investigation was to establish the frequency of contamination by enteric parasites in vegetables that are sold in the Central Market of Moyobamba during the year 2021. A total of 640 samples of vegetables distributed equally between: Lactuca sativa "lettuce", Brassica oleracea "cabbage", Apium graveolens "celery" and Allium fistulosum "chinese onion". For the detection of parasites, the samples were washed with distilled water, which was filtered and allowed to settle spontaneously, the sediment was centrifuged to which the Telemann and Sheather techniques were applied. It was found that 20,16% of the vegetables presented contamination by one or more species of enteroparasites, of which lettuce was the one that presented the highest frequency (37,21%), followed by cabbage (26,36%). The identified parasites and their respective frequencies were: Entamoeba spp., 49,44%; Blastocystis hominis, 23,99%; Ascaris lumbricoides, 16,24%; Giardia lamblia, 9,23% and Trichuris trichiura, 1,11%. This is the first record of contamination by intestinal parasites in vegetables sold in Moyobamba (Peru), so it is necessary to implement measures to improve the hygienic-sanitary quality of vegetables from cultivation to marketing in supply centers since these constitute an epidemiological factor in the chain of transmission of intestinal parasites. Finally, it was concluded that the frequency of enteroparasites in the vegetables studied was 21,26%; the vegetable species with the highest contamination was lettuce followed by cabbage; the most frequent species of enteroparasites were Entamoeba spp. and Blastocystis hominis and according to their origin, the highest percentage of vegetables with the presence of enteroparasites were those from the Lambayeque region followed by those from the San Martín region.